Intercultural dialogue to overcome the Clash of civilizations - Bartolino, Margherita (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2015)
This paper aims to find a solution to a relevant issue that modern societies have to face: how does people coming from different cultures can live side by side in the same society? This dissertation explains how an intercultural dialogue could be a reasonable response to face this problem. Not only co-operation among citizens is necessary, but it could be used to bring benefits for both the society and their citizens as well. It will be explained why modern societies should facilitate the process of an intercultural dialogue and how they could stimulate it trough his social and political channels.